Are Firm-Specific Advantages Location-Specific Too? - Erramilli, M. Krishna; Agarwal, Sanjeev; Kim, Seong-Soo (Journal of International Business Studies, 1997)
Much of the research on the role of firm-specific advantages on firms' subsidiary ownership preferences has been undertaken in the context of advanced-country multinationals, specifically U.S. MNCs. Research has found that U.S. firms derive ownership advantages from their size, experience, and technological and marketing superiority. Perhaps having operated in the most-developed and sophisticated home market, many U.S. firms generate unique skills that give them absolute advantages over firms in almost all foreign host locations. Developing-country MNCs do not have absolute ownership advantages similar to those of the U.S. firms. The relevance of a particular firm-specific characteristic for a developing-country MNC may be contingent not only upon the home-country characteristics, as in the case of U.S. MNCs, but also upon host-country characteristics. This study investigates the subsidiary ownership preferences among Korean MNCS and finds that the influence of three firm-specific advantages—technological intensity, product differentiation and capital intensity—on subsidiary ownership levels is contingent upon whether the subsidiary is located in a relatively less-developed or a more-developed country as compared to the home country. Although some authors have suggested that the influence of firm-specific advantages may be contingent upon the characteristics of both home- and host-country locations, empirical investigations to this effect have been nonexistent.